PENERAPAN MODEL PEMBELAJARAN KOOPERATIF UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SEKOLAH DASAR - Dian Camelia; Afwa Alsinatin Nadhifah; Nazar Eka Saputra; Devita Rizkia Ramadhani S; Ayu winda; Priyono Tri Febrianto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the implementation of cooperative learning models in improving social studies learning outcomes of fourth-grade elementary school students. The background of this research is the low student learning outcomes caused by the dominance of conventional teaching methods, which tend to make students passive and less engaged. This research uses a descriptive qualitative approach with a literature study method. The data were obtained from 20 national and international journal articles published within the last five years, focusing on various cooperative learning models such as Jigsaw, Make a Match, Student Teams Achievement Division (STAD), Numbered Heads Together (NHT), and others. The data were collected through academic databases and analyzed using content analysis techniques. The results show that the application of cooperative learning models consistently improves students' learning outcomes, both cognitively and socially. These models encourage active participation, collaboration, and meaningful learning experiences. Furthermore, the integration of interactive media and technology strengthens the effectiveness of these models. In conclusion, cooperative learning models are proven to be effective and relevant in enhancing social studies learning outcomes in elementary schools and can be adapted according to the characteristics of the material and students.